Footprint organization of chiral molecules on metallic surfaces - Uñac, Rodolfo Omar (2007)
We study the behavior of chiral molecules adsorbed on clean metallic surfaces using a lattice-gas model and Monte Carlo simulation. The aim is to model and simulate the structure (footprints and organization) formed by molecules on the surface as they adsorb. The model, which is applicable to chiral species like S- and R-alanine, or similar, discloses the conditions to generate different ordered phases that have been observed in experiments by other authors. In our model, each enantiomer may adsorb in two different configurations (species) and several effects are taken into account: inhibition, blockage of neighboring adsorptive sites (steric effects) and promotion of sites representing, in some sense, modifications in the surface properties due to molecule-surface interactions. These adsorption rules are inspired by the enantiomeric character of adsorbed species. We perform a systematic study of the different phases formed in order to qualitatively understand the mechanism for the formation of adsorbate structures experimentally found by other authors.